Road Safety Data Assessment in Viet Nam for the Establishment of a National Road Safety Observatory - Anh, Tran Thi Van; Burlacu, Alina F.; Small, Martin; Paala, Mirick; Duc, Nguyen Huu; Tri, Le Huy (World Bank, Hanoi, 2021)
The World Bank has been assisting the Government of Viet Nam (GoVN), through the National Traffic Safety Committee (NTSC), to establish a National Road Safety Observatory (NRSO) for Viet Nam, improve road safety data systems, and update the National Road Safety Strategy and Action Plan for Viet Nam. Input to the updated national strategy observed that there is insufficient attention given to the overall results framework (beyond simply the number of fatalities and serious injuries) that is required to achieve significant and sustainable reductions in serious road trauma. This reflects a need to strengthen both national governance and leadership arrangements for road safety, and road safety data systems (including road crash data systems), which are the focus of this report.